Costless Signalling in Financial Markets - FRANKE, GÜNTER (Journal of Finance, 1987)
ABSTRACT A costless, fully revealing signalling equilibrium is derived from two easily understandable conditions. The outsider‐rationality condition states that the outsiders relate the price that they offer to pay for a security inversely to the supply of this security, which they interpret as a quality signal. The no‐arbitrage condition requires that the marginal exchange rate for two securities be the same in both primary and secondary markets. These conditions restrict the firm's financing policy and have strong implications for the valuation of securities and of the total firm. A costless signalling equilibrium is obtained.